HIPERCARE Innovation Program Utilizing Butterfly Pea Flower As A Complementary Therapy Platform For Hypertension Patients In The Community - Subiantoro, Miftaqul Bilka; Azziyad, Muhammad Syafiq; Afriasih, Lya; Mauluddin, Gessa Tegar Syahrul; Naimah, Nurul Azimatun; Fauziah, Fatma (Caring: Jurnal Pengabdian Masyarakat, 2025)
Background:  Hypertension is one of the most common non-communicable diseases found in the community and often goes unnoticed until it causes serious complications. In Baureno Village, although health services are available, the community remains less concerned about early detection and proper management of hypertension. This condition indicates the need for an educational and mentoring platform, namely HIPERCARE (Hypertension Prevention, Management, Care, and Education). This activity aims to determine the effectiveness of health education and butterfly pea flower tea consumption in reducing blood pressure and improving the knowledge of individuals with hypertension. This community service programme was carried out in three stages. The first stage was the pre-activity phase, consisting of observation and an initial survey. The second stage was the implementation phase, which included health screening, counselling, demonstrations, and the implementation of the HIPERCARE platform integrated with a seven-day butterfly pea flower tea consumption programme as a non-pharmacological intervention. The third stage was the evaluation phase, conducted through blood pressure measurement and a pre–post knowledge test. The activities were conducted from 4–13 March 2025 in Baureno Village, Baureno District, Bojonegoro Regency, involving 95 participants with hypertension. The programme demonstrated a decrease in the proportion of participants with severe hypertension and an improvement in the proportion of those achieving a good level of knowledge. The HIPERCARE programme had a positive impact on increasing awareness and reducing blood pressure among individuals with hypertension. This initiative is expected to be applied in other communities or villages as a practical and sustainable promotive and preventive strategy.